MALAT-1, a Novel Noncoding RNA, and Thymosin β4 Predict Metastasis and Survival in Early-Stage Non-Small Cell Lung Cancer - Ji, Ping; Diederichs, Sven; Wang, Wenbing; Böing, Sebastian; Metzger, Ralf; Schneider, Paul M.; Tidow, Nicola; Brandt, Burkhard; Buerger, Horst; Bulk, Etmar; Michael Thomas; Wolfgang E. Berdel; et al. (Oncogene, 2003)
Early-stage non-small cell lung cancer (NSCLC) can be cured by surgical resection, but a substantial fraction of patients ultimately dies due to distant metastasis. In this study, we used subtractive hybridization to identify gene expression differences in stage I NSCLC tumors that either did or did not metastasize in the course of disease. Individual clones (n 1⁄4 225) were sequenced and quantitative RT–PCR verified overexpression in metastasizing samples. Several of the identified genes (eIF4A1, thymosin b4 and a novel transcript named MALAT-1) were demonstrated to be significantly associated with metastasis in NSCLC patients (n 1⁄4 70). The genes’ association with metastasis was stage- and histology specific. The Kaplan–Meier analyses identified MALAT-1 and thymosin b4 as prognostic parameters for patient survival in stage I NSCLC. The novel MALAT-1 transcript is a noncoding RNA of more than 8000nt expressed from chromosome 11q13. It is highly expressed in lung, pancreas and other healthy organs as well as in NSCLC. MALAT-1 expressed sequences are conserved across several species indicating its potentially important function. Taken together, these data contribute to the identification of early-stage NSCLC patients that are at high risk to develop metastasis. The identification of MALAT-1 emphasizes the potential role of noncoding RNAs in human cancer.